Cost benefit analysis of flexible and rigid pavements of rural roads using rice husk ash and stone dust as additives - Ponduri, Samatha; Rama Rao, M. (International Journal of Engineering and Technology, 2019)
In today scenario of Infrastructure development, Road network development plays an important role. Lack of stable ground for the construction of roads is very common especially when subgrade is made of expansive soil subjected to alternate swelling and shrinkage. Making of a suitable ground is a real challenging issue for Geotechnical Engineers. To overcome the difficulties experienced with problematic soil on one side and to make a path for safe disposal of waste materials on the other side, an at-tempt is needed to explore the possibilities of utilizing waste materials to improve the engineering behaviour of problematic soil.Disposal of waste materials on the landfill can be minimized if the waste which possess desirable properties can be utilized for various geotechnical application viz. reclamation of land and embankment construction etc. Rice husk ash and stone dust are such waste materials when blended with soil along with cement and lime separately can be of great advantage in reducing swell and shrinkage of expansive soils and make the ground more stable in consideration of rural road subgrades with problematic soils.This project works with the basic aim of laboratory mixing of rice husk ash and stone dust with lime and cement separately and variation of Atterberg limits, CBR were studied. Then by means of IRC SP 72-2015 and IRC SP62:2014 flexible and cement concrete pavement designs were made for improved CBR by using rice husk ash and stone dust as additives independently to cement and lime stabilized the soil. This project also aims at providing a cost-effective solution for rural subgrade by means of cost-benefit analysis of various mixes viz. soil â€“ lime- rice husk ash, soil - lime - stone dust mixes, soil-cement-rice husk ash and soil-cement-stone dust mixes.Â Â Â